Study on the Path of Improving the Employability of Special Groups of College Students in the Context of Three All-round Education - Cha, Siyue; Li, Hong (Transactions on Economics, Business and Management Research, 2023)
Special groups of college students are in a disadvantaged position in terms of employment due to the economic conditions of their families, the pressure of life and study, the external environment and other factors, so how to improve the employment rate of graduates from special groups of college students has become an urgent problem to be solved. Under the background of "Three all-round education", colleges and universities, society and families should make joint efforts to improve the employability of special groups of college students, implement personalized employment guidance, and provide a full range of employment services. The article discusses the meaning of college students' employability, analyzes the factors affecting the employability of special groups of college students, and explores effective ways to improve them.